2017
DOI: 10.1007/s10157-017-1467-9
|View full text |Cite
|
Sign up to set email alerts
|

Decline in estimated glomerular filtration rate is associated with risk of end-stage renal disease in type 2 diabetes with macroalbuminuria: an observational study from JDNCS

Abstract: These results suggest that a ≥30% decline in eGFR over 1 or 2 years adds prognostic information about risk for ESRD in patients with type 2 diabetes and macroalbuminuria, supporting the consideration of percentage decline in eGFR as a surrogate endpoint among macroalbuminuric cases in type 2 diabetes. On the other hand, our study suggests that additional analyses on the relationship between remission of macroalbuminuria and risk of ESRD are needed in type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…Our report also confirms that severely increased albuminuria is strongly predictive for progression to advanced renal disease or long‐term dialysis. Previous studies in Pima Indians and Japanese patients with type 2 diabetes showed that severely increased albuminuria predicts ESKD 34,35 . With regard to blood pressure this study confirms that high systolic blood pressures in T2DM are associated with a steep decline in kidney function 36 …”
Section: Discussionsupporting
confidence: 81%
“…Our report also confirms that severely increased albuminuria is strongly predictive for progression to advanced renal disease or long‐term dialysis. Previous studies in Pima Indians and Japanese patients with type 2 diabetes showed that severely increased albuminuria predicts ESKD 34,35 . With regard to blood pressure this study confirms that high systolic blood pressures in T2DM are associated with a steep decline in kidney function 36 …”
Section: Discussionsupporting
confidence: 81%
“…The incident nonproliferative diabetic retinopathy and progression from nonproliferative to proliferative diabetic retinopathy assessed by ophthalmologists as well as procedures involving vitrectomy or photocoagulation were counted as diabetic retinopathy outcomes. The outcomes of new or worsening nephropathy were defined as having any of the following: progression of albuminuria based on urinary albumin to creatinine ratio (incident microalbuminuria or progression from microalbuminuria to macroalbuminuria), doubling of serum creatinine, ≥30% decline in eGFR, or development of end-stage kidney disease [ 20 ]. Diabetic peripheral neuropathy was assessed by questionnaire, electromyography, or a nerve conduction study.…”
Section: Methodsmentioning
confidence: 99%
“…However, the clinical stage of albuminuria was also a significant risk factor for the occurrence of a CV event irrespective of the occurrence of a renal event. Studies in Japan have found that renal and cardiovascular outcomes were much more frequent in patients with albuminuria, and that those with a reduced eGFR without albuminuria had a relatively benign status 17–20 . Yokoyama et al 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Japan have found that renal and cardiovascular outcomes were much more frequent in patients with albuminuria, and that those with a reduced eGFR without albuminuria had a relatively benign status [17][18][19][20] . Yokoyama et al 21 reported that non-albuminuric DKD patients did not have a high risk of mortality, CVD events or renal function decline when non-albuminuric DKD was not accompanied by previous macrovascular complication.…”
Section: Discussionmentioning
confidence: 99%